(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2024)
The work, carried out through bibliographic, legislative and jurisprudential research, carried out by the deductive method, supports the imperative of conducting research with stem cells, to provide people with disabilities who suffer from certain diseases (cardiopathies, diabetes, blindness, dementia etc.), a chance to improve their quality of life. In addition to the constitutional right to healthcare, the text preaches the need to analyze the issue from the perspective of social inclusion of persons with disabilities, as recommended in principle hosted in article 3 of the International Convention on the Rights of Persons with Disabilities and its Optional Protocol, signed in New York, on March 30, 2007. So It proposes a hermeneutic turn around art. 5 of Law 11.105/2005, which regulates the limits of research with embryonic stem cells, a topic already object of a decision by the Supreme Court in ADI 3.510, when judges ruled for the constitutionality of the article. It concludes that therapeutic cloning does not instrumentalize a person in favor of others, therefore not contrasting with Kant’s ethics. The article also proposes a reinterpretation of art. 26 of Law 11.105/2005, when it comes to therapeutic cloning.